Optimalisasi Pemberdayaan Santri Melalui Program Eco Pesantren Berbasis Lingkungan, Kewirausahaan, Branding Dan Digitalisasi Di Pondok Pesantren Baitul Hikmah - Ririn Puspita Tutiasri; Nadhifah Bernice Tsaniyah; Mifa Amira Dewi; Sumrdjijati (LPPI UMN AL WASHLIYAH, 2025)
This community service program was implemented through a Thematic Community Service (KKN-T) activity with an Eco Pesantren approach at Baitul Hikmah Islamic Boarding School, Jember. The program aimed to enhance the capacity of students and administrators through limited-area organic farming training, compost and eco enzyme production, entrepreneurship training focusing on UMKM branding and 7P marketing strategy, public speaking training, digital financial management using Excel, and technology diffusion through eco design-based gate architecture. The implementation methods included training, community education, consultation, and science-technology diffusion. Evaluation was conducted through observation, interviews, and participant documentation. The results showed significant improvements in farming skills, design and marketing capabilities, public communication literacy, and digital financial management. Furthermore, the pondok gate design provided a concrete contribution to strengthening the pesantren's eco-friendly identity. This program demonstrated that the integration of practical and collaborative methods to improve the pesantren’s human resources. Sustainability is recommended through independent follow-up mentoring and ongoing internal monitoring by pesantren administrators.